Sperm storage and morphofunctional bases of the female reproductive tract of the snake Philodryas patagoniensis from southeastern Brazil - Rojas, Claudio Augusto; Barros, Verônica Alberto [UNESP]; Almeida-Santos, Selma Maria (Springer Nature, 2015)
Macroscopic and microscopic examination of the female reproductive tract of Philodryas patagoniensis was conducted in order to observe sperm storage structures and determine morphological changes throughout the reproductive cycle. The oviduct of P. patagoniensis is composed of the infundibulum (anterior and posterior), uterus, utero-vaginal junction, and vagina. The uterine epithelium showed constant secretory activity throughout the reproductive cycle, although increased production of secretory granules was observed in secondary vitellogenic females. Sperm storage occurs in the posterior infundibulum and utero-vaginal junction in pregnant, primary (postpartum), and secondary vitellogenic females. These data suggest that P. patagoniensis may be able to produce several clutches from a single mating. Sperm storage in the posterior infundibulum occurs in sperm receptacles, while in the utero-vaginal junction sperm is stored in crypts. Histochemical tests by periodic acid–Schiff revealed that both sperm storage sites increase the production of neutral carbohydrate-rich granules in the presence of sperm, similar to snakes from temperate regions. This is the first report of sperm storage in the posterior infundibulum of a neotropical snake.
Keywords: Dipsadidae; Histochemical reaction; Histology; Oviduct; Scanning electron microscopy